Insight and Treatment Attitude In Schizophrenic PatientsA Study on Indoor Cases from Three Tertiary Level Hospitals of Dhaka City (Journal of Armed Forces Medical College, Bangladesh, 2014)
Introduction: It is frequently reported that schizophrenic patients have poor insight into their course of illness. Poor insight has considerable value in predicting the long-term course of chronic mental disorders and it has impact on patients' compliance with treatment plans. Lack of insight is a common symptom of the acute phase of schizophrenia, being described in 97% of acute cases in the World Health Organization International Pilot Study of Schizophrenia. It will enhance awareness among all level of medical professionals for prompt diagnosis or at least early referral to psychiatrist and that will be helpful to reduce the sufferings and treatment cost of the schizophrenic patients. Objectives: It was a descriptive cross sectional study and was carried out to find out the relationship of levels of compliance and drug attitudes with insight of people with schizophrenia as lack of insight often results in non-adherence and so treatment failure. Materials & Methods: This study was carried out on 100 admitted schizophrenic patients from nominated hospitals. Among them 50 patients were acute (first episode) and 50 patients were relapsed (subsequent episode) schizophrenic patients. Purposive sampling technique was used. Purpose of the study & procedure were explained to all diagnosed schizophrenic patients (diagnosed by psychiatrist) & only those who gave consent were finally selected for the study. Insight and attitude to treatment was assessed by using the Insight and Treatment Attitude Questionnaire (ITAQ) Results: It is frequently reported that schizophrenic patients have poor insight into their illness. In this study total number of cases was 100; among them 50 were having first episode schizophrenia and 50 subsequent episodes of schizophrenia. Regarding age, 33% were below 20 years of age, 33% between 20 to 30 years of age, 19% between 30 to 40 years, 13% between 40 to 50 years and 2% above 60 years; 61% of the subjects were male and 39% were female. Most of the cases were students (31%), house-wives (25%) and unemployed personnel (23%). Rest were service personnel, day labourers, retired persons, business men and farmers. In collected sample, 65% were educated below SSC level and 35% above SSC and 53% were from urban area and 47% were from rural area. 51% were from lower middle class family, 37% of cases had positive family history of psychiatric illness. In graduates & beyond patients mean awareness of illness was 3.00 ± 3.32 and mean attitude to treatment was 4.29 ± 3.73. In lower income group mean awareness of illness was 1.50 ± 2.10 and attitude to treatment was 2.69 ± 2.48. Conclusion: Insight has been associated with greater expressed willingness to take medications, better adherence to prescribed medications. It is observed here that awareness of illness was more in middle class and attitude to treatment is more in lower middle class group so service provider will give more emphasis on this two groups for better outcome. DOI: http://dx.doi.org/10.3329/jafmc.v9i1.18722 Journal of Armed Forces Medical College Bangladesh Vol.9(1) 2013: 25-34